LANDSCAPE AND ORIENTATION OF MEGALITHIC CHAMBERS IN MECKLENBURG-VORPOMMERN (NORTH GERMANY): PHENOMENOLOGY PERSPECTIVE (Bentang Alam dan Orientasi Megalitik di Mecklenburg-Vorpommern Jerman Utara: Perspektif Phenomenologi) - Tolla, Marlin (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2014)
Phenomenological perspective is one of the approaches in archaeology especially applies to the use of sensory experiences of the past peoples through material cultures. Phenomenological approaches is based of some German philosopher such as Edmund Husserl, MartinHeidegger which put their attention to perceptions and knowledge which are based on experience of daily lives. Phenomenological approach have been produces a great impact through some works of archaeologist especialy from the group of Post-Procesualist such as Christian Tilley and others in attempt to interpretated the landscape phenomenon in Britain archaeological sites. In relations with that, the phenomenology approaches will be used to analysed the groups of megaliths chambers in Mecklenburg-Vorpommern (northern Germany) according to the cosmological significance.ABSTRAKPenomenologi adalah salah satu pendekatan yang digunakan dalam arkeolologi terutama dalam menganalisa ‘experience’ atau pengalaman manusia pada masa lalu melalui budaya material yang ditinggalkan. Pendekatan ini diadopsi dari filosof Jerman seperti: Edmund Husserl dan Martin Heidegger yang menekankan bahwa esensi dari presepsi manusia adalah terletak pada ‘pengalaman’ yang ditemukan di setiap hari. Pendekatan ini kemudian diadopsi oleh arkeolog terutama yang berasal dari grup Post-prosesualis seperti Christian Tilley dan lainnya terutama dalam menginterpretasikan arkeologi landskap. Merujuk pada hal ini, megalitik di Mecklenburg-Vorpommern diindikasikan sebagai ‘buah’ dari pengalaman oleh manusia pada masa lalu dalam menginterpretasikan alam sekitar mereka terutama dalam hubungannya dengan kosmologi.